Iqbal’s Ideas Regarding the New Perceptions of Space and Time - Baharuddin, Azizan (Intellectual Discourse, 2013)
In the context of Islam the subject of science and belief has always been part of its élan vital. From hundreds of Qur’ānic verses, Muslim scholars and thinkers have embarked on the exercise to understand scripture in the light of His creation (the study of nature or science). When talking about space and time in the empirical and spiritual sense it is indeed these "signs" that Iqbal was interested in. This paper presents some of the ideas Iqbal had elaborated upon regarding religion and science especially on the subject of the meaning and spiritual implications of the concepts of space and time.